An Approach to Neutrosophic Hyper Soft Rough Matrix and its Application - J. Boobalan; E. Mathivadhana (Neutrosophic Sets and Systems)
This paper introduces a novel of Neutrosophic Hyper Soft Rough Matrix (NHSRM). We discuss various operators on NHSRM such as addition, multiplication, scalar multiplication and complement. Additionally, we develop several properties, including associativity, distributivity and De Morgan’s laws, utilizing operators such as union, intersection, complement, arithmetic mean, weighted arithmetic mean, geometric mean, weighted geometric mean, harmonic mean and weighted harmonic mean. Further we propose a score function as part of this work. To demonstrate the application of the proposed work, a multi-attribute decision-making problem is considered. The score matrix obtained from three different operators are compared, and the results are illustrated graphically.